Role of the Middleman in Supporting of Oil Palm Smallholders' Community Performance: A Case Study in North Sumatra, Indonesia - Nurjanah, Danik; Anggrasari, Herdiana (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2023)
Oil palm agribusiness involves many upstream and downstream stakeholders, including the middleman in marketing activities. Traders play a significant role and influence the economy of oil palm farmers in Serdang Bedagai Regency. This research aims to evaluate the part of the middleman in supporting the performance of oil palm smallholders in Serdang Bedagai Regency, North Sumatra and the obstacles in marketing fresh fruit bunches (FFB) faced by farmers and the middleman. The samples of this study were 6 middlemen and 40 oil palm farmers. The sampling method used was purposive sampling. The method used in the analysis is a qualitative descriptive method, which explains the role of intermediaries in supporting the performance of smallholder oil palm farmers. The results showed that marketing support, capital and quality were the essential roles of the middleman as perceived by the smallholders. Apart from that, in the smallholder palm oil plantation, there are obstacles, namely in terms of price, road access and weight. Meanwhile, the barriers for the middlemen are in terms of price and buying and selling contracts. Policy recommendations for stakeholders include educating smallholder oil palm growers through counseling about access to information, improving access to the main roads in Serdang Bedagai Regency, periodic government monitoring, and drafting a written or legal sale and purchase agreement as not to harm both parties.